Analysis of Secure Medical Image Communication with Digital Signature and Reversible Watermarking - A. Umamageswari; G.R. Suresh (Institute of Advanced Engineering and Science, 2015)
Protection of Medical image contents becomes the important issue in computer network security. Digital Watermarking has becomes a promising technique for medical content authentication, it allows to embed relevant information with the image, which provides confidentiality, integrity and authentication by embedding Digital Signature (DS) with the Medical image. In this paper we focus on need for reversible watermarking, Medical Image Compression and security related problems in medical images, it comparing the performances of various lossless watermarking techniques for various medical image modalities like MRI (Magnetic Resonance Imaging), US (Ultrasonic), CT (Computed Tomography), Endoscopic and Angiographic images. Region of Interest (ROI) supporting lossless watermarking systems only considered for discussions. Performance of all lossless watermarking with Digital Signature is analyzed by means of four parameters Capacity Rate, PSNR (Peak Signal to Noise ratio), NPCR (Number of Pixel Change Rate) and Compression Ratio (CR). This Paper also introduces new mechanism for open network security for medical images. This lossless watermarking is responsible for recovering the altered medical image content of the system.